A Systematic Study of Cache Side Channels Across AES Implementations - Mantel, Heiko; Weber, Alexandra; Köpf, Boris (Engineering Secure Software and Systems, 2017)
While the AES algorithm is regarded as secure, many implementations of AES are prone to cache side-channel attacks. The lookup tables traditionally used in AES implementations for storing precomputed results provide speedup for encryption and decryption. How such lookup tables are used is known to affect the vulnerability to side channels, but the concrete effects in actual AES implementations are not yet sufficiently well understood. In this article, we analyze and compare multiple off-the-shelf AES implementations wrt. their vulnerability to cache side-channel attacks. By applying quantitative program analysis techniques in a systematic fashion, we shed light on the influence of implementation techniques for AES on cache-side-channel leakage bounds.